ANALISIS RISIKO PELAKSANAAN PEMBANGUNAN JALAN TOL BENOA – BANDARA – NUSA DUA - Ni Putu Mega Astiti; I N. Norken; IBN. Purbawijaya (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2015)
Benoa-Bandara-Nusa Dua toll road project is the first toll road project in Bali. This highway connects region Nusa Dua with Benoa Harbour area. Construction of toll roads-Benoa-Bandara-Nusa Dua is claimed as the fastest highway development in Indonesia as completed within 14 months. With time so short that the implementation of development it is necessary to research on the risks that arise in the implementation phase of the construction of the toll road The existence of the risks that arise in the implementation of toll road construction will directly impact the cost and development time. It is necessary in order to study the risks that might occur notably members of the dominant risk category can be used as a basis for decision making by the parties concerned to overcome the negative consequences that occur in the construction of toll roads. The research was conducted by means of interviews with various parties and has expert competence in the implementation of toll road construction to determine how the possibility (likelihood) against a variety of risks and to determine how much influences (Consequences) risk. The number of risks identified in this study was as many as 54 risks. The distribution of revenue risk of the project is a total of 18 (33.33%) classified as unacceptable risk, 25 (46.29%) classified as undesirable risk, 9 (16.67%) classified as acceptable risk, 2 (3.7%) classified as negligible risk. Handling risk (risk mitigation) is only performed on the dominant risks are risks that are categorized as unacceptable and undesirable. Risk mitigation conducted on a total of 18 risk unacceptable risk. 25 risk mitigation undesirable risk. Based on the results of this mitigation is then performed risk management ownership (ownership of risk) to the parties involved in the implementation of toll road construction project.